A Cardioplegic Solution with an Understanding of a Cardiochannelopathy - Min Jeong Ji; Jeong Hee Hong (MDPI AG, 2021)
Cardiac surgeries have been improved by accompanying developing cardioplegia solutions. However, the cardioplegia application presents an ongoing challenge with a view of a sufficiently restored cardiac function. In this review, we focus on the cardioplegia-induced mechanism and summarize the findings of studies undertaken to improve cardioprotective strategies. Currently, and somewhat surprisingly, relatively little is known about cardiac electrolyte regulation through channel physiology. We hope that an improved understanding of the electrolyte transport through ion channels/transporters and modulations of water channel aquaporins will provide an insight into cardiac channel physiology and a channel-based cardiac pathology of a cardiochannelopathy.